Epidemiology of Epstein-Barr virus in Malaysia - Norzuriza, MR; Kon Ken, W; Mohammad, M; Isahak, I; Rahman, MM (Bangladesh Veterinarian, 2010)
An epidemiological investigation was carried out on patients reported to Hospital University Kebangsaan Malaysia (HUKM) suspected to be carriers of Epstein-Barr virus from July 2005 to June 2006. A total of 402 patients' sera were analyzed by Enzyme Immunoassay with Kit Enzygnost® by automated BEP® 2000 instrument. Of these 91.3% were found to carry Epstein-Barr virus (EBV) antibodies. Among these, 90.4%of male and 92.2% of female patients were positive: the difference was not significant. Considering community, 91.9% of Malay, 91.9% of Chinese, 75% of Indian and 93.3% of others were positive: the differences were not significant. Among the age groups, 77.5% of 0-20 year-olds, 98.6% of 21-40 year-olds, 96% of 41-60 year-olds and 100% of those above 60 years of age were positive: these differences were significant (p<0.005). No significant difference in the prevalence of EBV antibodies existed between the months of sampling. In the present study, EBV-specific IgG and IgM antibodies were determined. The proportion of samples positive to IgM was much less than those positive to IgG. DOI: 10.3329/bvet.v25i2.4622 Bangl. vet. 2008. Vol. 25, No. 2, 82-87